Innovative synthesis of Tm³⁺/Er³⁺-doped Yb-YGG single crystals for upconversion-based white light emission - Albino, Leonardo Vieira [UNESP]; Delendatti, Agustín [UNESP]; Caixeta, Fábio José [UNESP]; Lodi, Thiago Augusto [UNESP]; Franco, Douglas Faza [UNESP]; Pinto, Camila Batista; Ellena, Javier Alcides; Nalin, Marcelo [UNESP] (Elsevier, 2024)
In recent years, there has been a growing interest in developing advanced materials for photonics applications, particularly for efficient white light emission, which is crucial for technologies like solid-state lighting and display devices. One interesting approach for emitting white light is Upconversion (UC) luminescence. This study focuses on synthesis, by a new and alternative method, and characterization of yttrium ytterbium gallium garnet (Yb-YGG) single crystals, specifically Y1.8Yb1.2Ga5O12, doped with various concentrations of Er3+ and Tm3+ ions. These crystals were studied intending to enhance UC luminescence properties for white light generation by modifying their respective emissions in the red, green, and blue (RGB) regions. Unlike traditional methods such as Czochralski, these crystals were produced by controlled nucleation and growth through gradual cooling of a specific glass mixture, leading to Yb-YGG single crystals doped with different concentrations of Yb3+, Er3+, and Tm3+ ions. By optimizing the Yb3+/Tm3+/Er3+ ratio, the study allowed to obtain micrometric single crystals that efficiently emit white light via UC. The crystals were characterized by X-ray diffraction, optical and electronic microscopies, EDS and luminescence spectroscopy.
Keywords: Glasses; Rare earth; Upconversion; White light emitter; Ytterbium yttrium gallium garnet